Preventing Chronic Kidney Disease: The Role of Community-Based Interventions - Sourabh Sharma,; Rasha Darwish,; Madhur Verma,; Sanjay Kalra, (Journal of the Pakistan Medical Association, 2025)
Chronic Kidney Disease (CKD) is a growing public health crisis, driven by the increasing prevalence of metabolic disease. Without timely detection and intervention, CKD can progress to end-stage kidney disease, leading to significant morbidity and mortality. In line with the theme of World Kidney Day (WKD) 2025, "Are Your Kidneys OK? Detect Early, Protect Kidney Health," this article explores community-based interventions as a key strategy in preventing CKD. Awareness campaigns, early screening programmes, and integration of kidney care with primary health care are essential for mitigating CKD risk. Policymakers, healthcare professionals, and community organisations must collaborate to implement sustainable strategies that promote kidney health and reduce CKD-related burden. Keywords: Chronic kidney disease, community-based interventions, health education, lifestyle, kidney screening, preventive medicine